2000
DOI: 10.1063/1.1333689
|View full text |Cite
|
Sign up to set email alerts
|

Optically pumped InGaN/GaN lasers with wet-etched facets

Abstract: Optically pumped laser action is demonstrated in InGaN/GaN double heterostructure lasers with wet-etched facets. The facets are formed by a two-step etching process which creates vertical facets with less than 5 nm roughness. The first step, photoenhanced electrochemical wet etching, is used to define the laser cavities. The second step reduces the facet roughness by crystallographic wet chemical etching. Lasing is demonstrated by an increase in the differential quantum efficiency, linewidth narrowing, and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…[11][12][13][14][15] Of these methods, cleaving has produced the smoothest facet surfaces with root-mean-square (RMS) roughness values on the order of 1 nm for GaN-based laser diodes (LDs) grown on SiC. 3 However, etched facets have a number of advantages, including applicability to laser epilayers grown on substrates such as sapphire that do not have common cleavage planes, and the potential for on-wafer laser testing.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Of these methods, cleaving has produced the smoothest facet surfaces with root-mean-square (RMS) roughness values on the order of 1 nm for GaN-based laser diodes (LDs) grown on SiC. 3 However, etched facets have a number of advantages, including applicability to laser epilayers grown on substrates such as sapphire that do not have common cleavage planes, and the potential for on-wafer laser testing.…”
Section: Introductionmentioning
confidence: 99%
“…Stocker et al reported a selective wet chemical etching method to form smooth {10true1¯0} plane ( m ‐plane) of GaN, and the rms roughness was estimated on the order of 1 nm . GaN laser diodes with wet‐etched facets were reported to increase the facet reflectivity and reduce the threshold power/current density . And wet etching in alkaline solution was adopted to reduce scattering loss of AlN waveguides .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if the FIB method is to be used for fabricating microdisk mesa structures, the tremendous sidewall damages caused by energetic Ga þ ion bombardment must be taken into account. As all dry-etch methods will damage the sidewalls with different extents, there are also reports of using chemical wet-etching methods such as highly anisotropic photoenhanced wet-etching [97,98] or crystallographic wetetching [99,100] to fabricate GaN slab with low-damage smooth sidewalls. However, control of microdisk geometry using wet-etching methods remains to be challenging.…”
Section: Feature Articlementioning
confidence: 98%